Sulfur-doped composite hard carbon material as well as preparation method and application thereof

By introducing sulfur atoms into the hard carbon negative electrode material and surface modification, the carbon layer spacing and specific capacity of hard carbon are improved, the rate performance of sodium ion batteries is improved, and the performance limitation problem caused by the small layer spacing of traditional hard carbon materials is solved.

CN119674063AActive Publication Date: 2025-03-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311578959.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2023-11-23
Publication Date
2025-03-21
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

Due to the small layer spacing of traditional hard carbon anode materials, the irreversible adsorption of sodium ions is limited, limiting the specific capacity and first-time Coulomb efficiency of sodium ion batteries, and the rate performance is poor.

Method used

By using sulfonated resin as a carbon source and sulfur source, non-metallic sulfur atoms are introduced using in-situ doping technology to increase the carbon layer spacing of hard carbon, and surface pre-coated modification of the sulfonated resin through a biomass carbon source to reduce specific surface area and defect locations.

Benefits of technology

The specific capacity of hard carbon materials has been improved, the first Coulomb efficiency and the rate performance enhancement have been enhanced, and the requirements of few defects and large layer spacing of sodium ion battery negative electrode materials have been solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674063A_ABST
    Figure CN119674063A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-doped composite hard carbon material as well as a preparation method and application thereof. Sulfonated resin is used as a carbon source and a sulfur source, and non-metal sulfur atoms with the atomic radius larger than that of carbon are doped in situ, so that the carbon layer spacing of hard carbon is increased, and the rate capability of the hard carbon is improved; and the sulfonated resin is subjected to surface pre-coating modification by using a cheap biomass carbon source, so that the specific surface area and defect sites of hard carbon are reduced, the number of closed pores is increased, and the specific capacity and the first coulombic efficiency of the hard carbon are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a sulfur-doped composite hard carbon material and a preparation method and application thereof, belonging to the field of hard carbon materials. Background Art

[0002] With the continuous exploitation and consumption of fossil energy around the world, fossil resources are becoming increasingly scarce, and environmental pollution and greenhouse effect are becoming increasingly serious. Therefore, it is necessary to vigorously develop clean energy such as solar energy, wind energy, and tidal energy. However, due to the constraints of weather, location and time, the large-scale application and popularization of these clean energy sources require supporting large-scale energy storage systems. Secondary batteries are a good choice for large-scale energy storage due to their high energy density and conversion efficiency. Lithium-ion batteries have been widely used in power batteries and other fields due to their advantages such as high energy density and long cycle life. However, limited lithium resources and rising raw material prices have severely restricted the application of lithium-ion batteries in the field of large-scale energy storage.

[0003] Compared with lithium-ion batteries, sodium-ion batteries (SIBs) have shown broad application prospects in the field of large-scale energy storage due to their high resource abundance, low cost and high safety. Compared with lithium ions, sodium ions have a larger radius, so the traditional lithium battery graphite anode materials (interlayer spacing 0.334nm) and soft carbon anode materials (interlayer spacing <0.36nm) have low sodium storage capacity and first coulombic efficiency due to their small interlayer spacing, which limits their practicality. In contrast, hard carbon anode materials have a larger interlayer spacing >0.38nm, so they have a higher sodium storage capacity (300mAh g-1), a lower sodium storage platform (~0.1V), and good cycle stability, and are considered to be very potential commercial anode materials for sodium ion batteries. However, the abundant defect sites on the hard carbon anode will lead to irreversible adsorption of sodium ions, resulting in a decrease in specific capacity and first coulombic efficiency. In addition, since the carbon interlayer spacing of traditional hard carbon is still relatively small, its rate performance is poor. Therefore, how to reduce defects and increase interlayer spacing is the key way to develop hard carbon negative electrode materials for sodium ion batteries with high specific capacity and good rate performance. Summary of the invention

[0004] According to one aspect of the present application, a method for preparing a sulfur-doped composite hard carbon material is provided, wherein a sulfonated resin is used as a carbon source and a sulfur source, and the carbon interlayer spacing of the hard carbon is increased by in-situ doping with non-metallic sulfur atoms having an atomic radius larger than that of carbon, thereby improving the rate performance of the hard carbon; and the sulfonated resin is surface-pre-coated and modified with a cheap biomass carbon source to reduce the specific surface area and defect sites of the hard carbon, thereby improving the specific capacity and first coulombic efficiency of the hard carbon, thereby solving the problem of how to prepare a hard carbon negative electrode material for a sodium ion battery with fewer defects and a large interlayer spacing.

[0005] This application adopts the following technical solutions:

[0006] A method for preparing a sulfur-doped composite hard carbon material comprises the following steps:

[0007] S1: mixing a sulfonated resin and a solution containing a polyol to form a solid-liquid mixture;

[0008] S2: placing the solid-liquid mixture obtained in step S1 in a sealed container and heating the mixture for reaction to obtain a modified sulfonated resin;

[0009] S3: cracking and carbonizing the modified sulfonated resin obtained in step S2 to obtain the sulfur-doped composite hard carbon material.

[0010] Optionally, the polyol is selected from at least one of glucose, sucrose, glycerol, sorbitol, and ascorbic acid;

[0011] Optionally, the content of polyhydroxy compound in the polyhydroxy compound solution is 5 to 60 wt %.

[0012] Optionally, the content of polyol in the polyol solution is selected from any value of 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, or any range therebetween.

[0013] Optionally, the sulfonated resin is selected from at least one of sulfonated polystyrene resin, sulfonated phenolic resin and sulfonated lignite resin.

[0014] Optionally, in step S1, the weight ratio of the polystyrene-based sulfonated resin to the solution of the polyhydroxy compound is 0.1 to 5:1.

[0015] Optionally, in step S1, the weight ratio of the polystyrene-based sulfonated resin to the solution of the polyhydroxy compound is selected from any value of 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, or any range therebetween.

[0016] Optionally, in step S2, the conditions for the heating reaction include: the reaction temperature is 80 to 250° C., and the reaction time is 0.5 to 24 hours.

[0017] Optionally, in step S2, the temperature of the heating reaction is selected from any value of 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 230°C, 250°C, or any range therebetween.

[0018] Optionally, in step S2, the heating reaction time is selected from any value of 0.5h, 5h, 10h, 15h, 20h, 24h, or any range therebetween.

[0019] Optionally, in step S3, the cracking conditions include: being carried out in an inert gas atmosphere, the cracking temperature is 300 to 600° C., and the cracking time is 0.5 to 8 hours.

[0020] Optionally, in step S3, the cracking temperature is selected from any value of 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, or any range therebetween.

[0021] Optionally, in step S3, the carbonization conditions include: being carried out in an inert gas atmosphere, the carbonization temperature is 800 to 1600° C., and the carbonization time is 0.5 to 12 hours.

[0022] Optionally, the inert gas atmosphere is selected from at least one of nitrogen, argon and helium.

[0023] Optionally, in step S2, the heating reaction further includes filtering and drying;

[0024] The drying conditions include: a temperature of 100 to 250° C. and a drying time of 1 to 12 hours.

[0025] According to another aspect of the present application, there is provided a sulfur-doped composite hard carbon material prepared by the above preparation method, wherein the mass content of sulfur in the sulfur-doped composite hard carbon material is 0.1 to 10%;

[0026] Optionally, the specific surface area of ​​the sulfur-doped composite hard carbon material is 0.1 to 50 m 2 / g.

[0027] Optionally, the carbon interlayer spacing of the sulfur-doped composite hard carbon material is 0.37-0.45 nm.

[0028] According to another aspect of the present application, a negative electrode material is also provided, comprising the sulfur-doped composite hard carbon material according to claim 8.

[0029] According to another aspect of the present application, a sodium ion battery is provided, comprising the negative electrode material according to claim 9.

[0030] The beneficial effects of this application include:

[0031] The preparation method provided in the present application has a simple preparation process, and the obtained composite hard carbon has a small specific surface area, few defects, and a large carbon layer spacing. The sodium ion battery prepared as a negative electrode material has a high specific capacity, a high first coulombic efficiency, and a high rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1This is a transmission electron microscope image of the composite hard carbon material obtained in Example 1.

[0033] Figure 2 This is the nitrogen physical adsorption curve of the composite hard carbon material obtained in Example 1. DETAILED DESCRIPTION

[0034] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0035] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0036] Example 1

[0037] S1: dispersing 10 g of sulfonated polystyrene resin in 50 g of 20% by mass glucose solution to form a solid-liquid mixture;

[0038] S2: the solid-liquid mixture is transferred into an autoclave, reacted at 180°C for 12 hours, cooled to room temperature, filtered to obtain a solid, and dried at 120°C to obtain a modified resin;

[0039] S3: placing the modified resin in a nitrogen atmosphere, heating it to 400°C, and keeping the temperature constant for 2 hours to obtain a low-temperature cracking product;

[0040] S4: placing the low temperature cracking product in a nitrogen atmosphere, heating it to 1200° C., and keeping the temperature constant for 2 hours to obtain a composite hard carbon material. The sulfur content of the obtained hard carbon material is 3.4%.

[0041] Figure 1 This is a transmission electron microscope image of the composite hard carbon material obtained in Example 1, and the carbon layer spacing is 0.39 nm.

[0042] Figure 2 This is the nitrogen physical adsorption curve of the composite hard carbon material obtained in Example 1, with a specific surface area of ​​26 m 2 / g.

[0043] Example 2

[0044] The method is basically the same as Example 1, except that the concentration of the glucose solution in S1 is increased to 60%, and the rest is exactly the same as Example 1.

[0045] The specific surface area of ​​the composite hard carbon material obtained in Example 2 is 6 m 2 / g, the carbon layer spacing is 0.39nm, and the sulfur content is 2.7%.

[0046] Example 3

[0047] It is basically the same as Example 1, except that the mass of the 20% glucose solution in S1 is replaced with 5 g, and the rest is exactly the same as Example 1.

[0048] The specific surface area of ​​the composite hard carbon material obtained in Example 3 is 48 m 2 / g, the carbon layer spacing is 0.37nm, and the sulfur content is 3.7%.

[0049] Embodiments 4 to 7

[0050] The method is basically the same as Example 1, except that the glucose solution in S1 is replaced with sucrose, glycerol, sorbitol and ascorbic acid in sequence, and the rest is exactly the same as Example 1.

[0051] The specific surface areas of the composite hard carbon materials obtained in Examples 4 to 7 are 24 m 2 / g, 41m 2 / g, 37m 2 / g and 31m 2 / g, the carbon layer spacing is 0.38nm, 0.37nm, 0.39nm, and 0.39nm respectively, and the sulfur content is 3.64%, 3.21%, 3.68%, and 3.79% respectively.

[0052] Embodiments 8 to 9

[0053] It is basically the same as Example 1, except that the reaction temperature in S2 is replaced with 80°C and 250°C respectively, and the rest is exactly the same as Example 1.

[0054] The specific surface areas of the composite hard carbon materials obtained in Examples 8 to 9 are 39 m 2 / g and 13m 2 / g, the carbon interlayer spacing is 0.37nm and 0.43nm, and the sulfur content is 2.9% and 4.67%, respectively.

[0055] Example 10

[0056] It is basically the same as Example 1, except that the reaction time in S2 is replaced by 24h, and the rest is exactly the same as Example 1.

[0057] The specific surface area of ​​the composite hard carbon material obtained in Example 10 is 11 m 2 / g, the carbon layer spacing is 0.45nm, and the sulfur content is 6.77%.

[0058] Embodiment 11

[0059] It is basically the same as Example 1, the only difference is that the cracking temperature in S3 is replaced by 600°C, and the rest is exactly the same as Example 1.

[0060] The specific surface area of ​​the composite hard carbon material obtained in Example 11 is 34 m 2 / g, the carbon layer spacing is 0.38nm, and the sulfur content is 3.7%.

[0061] Example 12

[0062] It is basically the same as Example 1, the only difference is that the carbonization temperature in S3 is replaced by 1500° C., and the rest is exactly the same as Example 1.

[0063] The specific surface area of ​​the composite hard carbon material obtained in Example 12 is 0.5 m 2 / g, the carbon layer spacing is 0.39nm, and the sulfur content is 4.3%.

[0064] Embodiment 13

[0065] The method is basically the same as Example 1, except that the sulfonated polystyrene resin in S1 is replaced by sulfonated phenolic resin, and the rest is exactly the same as Example 1.

[0066] The specific surface area of ​​the composite hard carbon material obtained in Example 13 is 7.5 m 2 / g, the carbon layer spacing is 0.383nm, and the sulfur content is 6.9%.

[0067] Comparative Example 1

[0068] The process is basically the same as Example 1, except that the reaction stage in the autoclave in S2 is omitted, and the rest is exactly the same as Example 1.

[0069] The specific surface area of ​​the composite hard carbon material obtained in Comparative Example 1 is 68 m 2 / g, the carbon layer spacing is 0.37nm, and the sulfur content is 0.7%.

[0070] Comparative Example 2

[0071] The method is basically the same as Example 1, except that the glucose solution in S1 is replaced with deionized water, and the rest is exactly the same as Example 1.

[0072] The specific surface area of ​​the composite hard carbon material obtained in Comparative Example 2 is 493 m 2 / g, the carbon layer spacing is 0.35nm, and the sulfur content is 0.05%.

[0073] Comparative Example 3

[0074] It is basically the same as Example 1, the only difference is that the cracking temperature in S3 is replaced by 250°C, and the rest is exactly the same as Example 1.

[0075] The specific surface area of ​​the composite hard carbon material obtained in Comparative Example 3 is 137 m 2 / g, the carbon layer spacing is 0.363nm, and the sulfur content is 2.1%.

[0076] Comparative Example 4

[0077] It is basically the same as Example 1, the only difference is that the carbonization temperature in S3 is replaced by 700° C., and the rest is exactly the same as Example 1.

[0078] The specific surface area of ​​the composite hard carbon material obtained in Comparative Example 4 is 211 m 2 / g, the carbon layer spacing is 0.372nm, and the sulfur content is 11.8%.

[0079] Example 13 Sodium Electrolyte Negative Electrode Performance Test Experiment

[0080] The composite hard carbon, conductive carbon black and sodium carboxymethyl cellulose prepared in the above examples and comparative examples were mixed in deionized water at a weight ratio of 80:10:10, ground into a paste, and applied to a copper foil current collector. After drying at 80°C for 12 hours, a number of pole pieces with a diameter of 12 mm were cut out with a cutting machine, weighed, and the mass of the hard carbon material (active material) was calculated. Then, in an argon protection glove box, a metal sodium sheet was used as the positive electrode, a glass fiber was used as the diaphragm, and a 1 mol / L NaPF6 / DEC:EC solution was used as the electrolyte to assemble a 2032 button half-cell. The sodium ion half-cell was charged and discharged in a constant current charge and discharge mode, with a voltage range of 1.0 to 4.2 V, and the sodium charge and discharge performance of the hard carbon material under different current densities (i.e., rates) was tested. The results are listed in Table 1.

[0081] Table 1 Electrical property test results of hard carbon sodium obtained from some examples and comparative examples.

[0082]

[0083] It can be seen from Table 1 that the sulfur-doped composite hard carbon material prepared by the technology of the present invention has the advantages of high specific capacity and good rate performance.

[0084] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a sulfur-doped composite hard carbon material, characterized in that: The steps include: S1: mixing a sulfonated resin and a solution containing a polyol to form a solid-liquid mixture; S2: placing the solid-liquid mixture obtained in step S1 in a sealed container and heating the mixture for reaction to obtain a modified sulfonated resin; S3: cracking and carbonizing the modified sulfonated resin obtained in step S2 to obtain the sulfur-doped composite hard carbon material.

2. The preparation method according to claim 1, characterized in that: In step S1, the polyol is selected from at least one of glucose, sucrose, glycerol, sorbitol, and ascorbic acid; Preferably, the content of polyhydroxy compound in the polyhydroxy compound solution is 5 to 60 wt %; Preferably, the sulfonated resin is selected from at least one of sulfonated polystyrene resin, sulfonated phenolic resin and sulfonated lignite resin.

3. The preparation method according to claim 1, characterized in that: In step S1, the weight ratio of the polystyrene-based sulfonated resin to the solution of the polyhydroxy compound is 0.1 to 5:

1.

4. The preparation method according to claim 1, characterized in that: In step S2, the conditions for the heating reaction include: the reaction temperature is 80 to 250°C, and the reaction time is 0.5 to 24 hours.

5. The preparation method according to claim 1, characterized in that: In step S3, the cracking conditions include: being carried out in an inert gas atmosphere, the cracking temperature is 300-600° C., and the cracking time is 0.5-8 hours.

6. The preparation method according to claim 1, characterized in that: In step S3, the carbonization conditions include: being carried out in an inert gas atmosphere, the carbonization temperature is 800 to 1600° C., and the carbonization time is 0.5 to 12 hours.

7. The preparation method according to claim 1, characterized in that: In step S2, after the heating reaction, filtering and drying are also included; The drying conditions include: a temperature of 100 to 250° C. and a drying time of 1 to 12 hours.

8. The sulfur-doped composite hard carbon material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: In the sulfur-doped composite hard carbon material, the mass content of sulfur element is 0.1 to 10%; Preferably, the specific surface area of ​​the sulfur-doped composite hard carbon material is 0.1 to 50 m 2 / g; Preferably, the carbon interlayer spacing of the sulfur-doped composite hard carbon material is 0.37-0.45 nm.

9. A negative electrode material, characterized in that: The sulfur-doped composite hard carbon material according to claim 8.

10. A sodium ion battery, characterized in that: Comprising the negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Composite negative electrode active material, preparation method thereof and negative electrode

    CN109962213A

  • Porous nano lithium iron phosphate composite material and preparation method thereof

    CN111211311A

  • Sulfur-doped hard carbon material based on calcium sulfur fixation strategy as well as preparation method and application of sulfur-doped hard carbon material

    CN115425195A

  • Hard carbon negative electrode material and preparation method and application thereof

    CN116477599A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    KR1020130107892A

Cited By

  • Sulfur-doped hard carbon material as well as preparation method and application thereof

    CN120736509A

  • A sulfur-doped hard carbon material, a preparation method and application thereof

    CN120736509B